Cochlear implantation after canal wall down mastoidectomy — Outcomes after partial mastoid obliteration. Issue 4 (August 2019) - Balk, Matthias; Schwarz, David; Wolber, Philipp; Anagiotos, Andreas; Gostian, Antoniu-Oreste
Abstract: Objective: To describe and evaluate the partial mastoid obliteration of the so-called radical mastoid cavity after canal-wall down mastoidectomy (CWD) for cochlear implantation (CI) compared to overclosure of the external ear canal as two stage procedures. Methods: Out of 1020 patients undergoing cochlear implantation between January 1st, 2003 and June 15th, 2016 at the Department of Otolaryngology, Head & Neck Surgery, University Hospital Cologne, eight patients underwent obliteration of the radical cavity prior to cochlear implantation. In four additional patients, the external ear canal was overclosed prior to cochlear implantation. Results: Patients undergoing partial mastoid obliteration (five ♀, 4 left ears) and overclosure of the external ear canal (one ♀, 3 left ears) averaged 56 years and 61 years, respectively. The radical cavities had been present for 21.8 years on average before partial obliteration and for 19.5 years before overclosure. Cochlear implantation following mastoid obliteration was performed after a mean period of 5.1 months and 3.8 months after overclosure. After partial mastoid obliteration, complete insertion of all electrodes was achieved and the clinical courses were uneventful for all patients. Likewise, no patient revealed any complications after overclosure of the external ear canal. Conclusion: Partial mastoid obliteration with bone paté and cartilage after canal wall down mastoidectomy can be advocated as a feasible alternative technique that allows for a safe subsequent cochlear implantation.